Cronicle of an announced matricide - Bravo-Villasante, María Ávila (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2017)
The purpose of this article is to show how the complex relationships between the third wave and the preceding feminism come from accepting a monolithic version created on the second wave. We begin by analyzing the term postfeminism, delimiting the term polysemy in its popular sense and its philosophical sense. After this process of disambiguation, we will analyze the foundational narratives of the third wave with the objective of highlighting some of its fundamental characteristics and analyzing to what extent it is debtor of a distorted version of the second wave. This analysis will lead us to analyze the rereading of Naomi Wolf and the difficulties of her new version of feminism - what she called “feminism of power”. We will try to show how the acceptance of this created ad hoc image of the second wave carries unintended consequences for the third wave, what about black and mestizo feminisms? Does not their exclusion lead to incurring the same error as that accused of the second wave? To conclude, we will attempt to account for the meta-polemics that arise within the feminism of the third wave. To do this, we will take as a common thread the hip-hop movement, a suburbia movement of African and African American roots linked to the emergence of the third wave.
Keywords: second wave; post-feminism; third wave